Strech-Press Method. An innovative technique of injection and pressing of detached plasters - Wichterlová, Zuzana (Univerzita Pardubice, 2022)
Many Renaissance sgraffito facades in the Czech Republic were uncovered and rediscovered during the last century. After removal of the secondary layers, the main problem appeared to be the condition of the original plasters, namely their poor adhesion, often connected with bad cohesion of the first coat. In the past, restorers used different approaches to that but over time, most of the steps proved to be unsuccessful or even destroying for the original plaster. Since 1997, we have restored many sgraffito facades. On all of them, we have dealt with similar problems of detached plasters connected with unsuitable or insufficient interventions of previous restorers. We had to search for some new approaches for in-depth consolidation of plasters, filling of gaps with a grouting material and pressing the plaster back to the wall. In the contribution, an innovative technique of pressing of detached plasters during injection (“Stretch-Press Method”) is described.
Strech-Press Method. Prakovací metoda. Inovativní technika injektáže a tlakování oddělených omítek.
Keywords: strech-press; method; injection; pressing; detached; plasters; grouting; sgraffito; wall painting; conservation; prakovací metoda; injektáž; tlakování; oddělené; omítky; sgrafito; nástěnná malba; konzervace